Myanmar Climate-Smart Agriculture Strategy - Hom NH; Htwe NM; Hein Y; Than SM; Kywe, M.; Htut T (2015)
Myanmar has committed to apply CSA to contribute to regional food security and environmental protection during the 24th ASEAN Summit on May 10, 2014. The Myanmar CSA strategy encompasses the development of technical, policy and investment conditions to achieve a sustainable agricultural development for food security and nutrition through climate-resilient and sustainable agriculture. Myanmar’s CSA strategy aims to be socially, culturally and politically appropriate, environment-friendly and economically feasible to promote and attain sustainable agriculture, food security and nutrition, agricultural development and climate change adaptation and mitigation. Myanmar’s CSA strategy also aims to provide context and analysis for addressing agriculture in international climate negotiations to better inform climate negotiators and other stakeholders by identifying options and unpacking issues of interest.